Analisis Kepatuhan Aksesibilitas Web Pemerintah Provinsi DIY Berdasarkan Standar WCAG 2.1. dengan WAVE API : Analysis of the Accessibility Compliance of the Yogyakarta Provincial Government's Website Based on WCAG 2.1 Standards with the WAVE API - Nurrohmah, Isnaeni (Information Technology and Science (ITScience), 2026)
Digital transformation requires the government to provide inclusive services for all people, including people with disabilities. However, a paradox often arises between the excellence of visual communication and compliance with technical accessibility standards. This study aims to evaluate the level of accessibility compliance of the Yogyakarta Provincial Government website (jogjaprov.go.id)—winner of the 2025 Public Relations Media Award—with the Web Content Accessibility Guidelines (WCAG) 2.1 standard. Using a quantitative descriptive design, this study automatically evaluates 30 purposively selected sample pages using the WAVE API to map the website's quality against the POUR (Perceivable, Operable, Understandable, Robust) principles. The results show excellent aggregate performance with an average AIM score of 9.1. However, in-depth analysis reveals non-compliance with accessibility principles on the main page (homepage), which has the lowest AIM score (5.1) due to 26 errors and 12 contrast errors.Furthermore, the most significant finding indicates the presence of Institutionalized Accessibility Barriers in the form of systemic violations of heading structures (h1 issues) on 96.7% of pages, which proves a structural deficit in the core template. Theoretically, this study introduces the concept of the Intra-domain Accessibility Divide, in which a gap in access quality arises within a domain due to unequal development priorities between aesthetics and inclusivity. The policy implications call for reforming government award assessment criteria and integrating WCAG standards into the system development life cycle (SDLC) to realize truly inclusive digital governance.